Congenital immature teratoma in infant - Piotr Rzepniewski; Natalia Gołuchowska; Joanna Schreiber-Zamora; Bożena Kociszewska-Najman; Michał Brzewski (Termedia Publishing House, 2022)
Teratomas are rare neoplasms. They account for 3% of all childhood tumors; 40-70% of them are located in the sacrococcygeal and presacral regions. Head and neck locations of the tumor are uncommon, account for only 2%. This article presents a case of a Polish Caucasian male infant born at 30 weeks of gestation, from the 3rd pregnancy, the first delivery by c-section. The infant's general condition was very severe. Birth weight was 2980 g. A large craniofacial tumor was prenatally detected in the newborn, with the suspicion of immature teratoma, which was later confirmed in postnatal examinations. The infant was operated on the 2nd day of life and the tumor size was 25-30 cm. After the surgery, birth weight decreased to 1600 g. Imaging tests provides prenatal diagnosis of craniofacial teratomas, which enables to plan early surgical treatment of the newborn with appropriate postoperative care, which increases the chances of survival.